Penghimpunan dan Penyaluran Dana PT. Bank Syariah Indonesia - Tadjuddin Malik (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
PT. Bank Syariah Indonesia as a business-oriented financial institution carries out activities to collect funds from the public and then lends them back into the community or the business world. The aims of this research is to comprehend how to collect funds from the public and lends them back into the community or the business world at PT. Bank Syariah Indonesia. Research and the gather of data and information were carried out through interviews and observations of several customers as well as document research through literature and also internet on the Financial Statements published on December 31, 2020 and March 31, 2021 (consolidated balance sheet of PT. Bank Syariah Indonesia’s branches). Data that has been summarized, classified and analyzed using qualitative and quantitative methods. The results showed that the implementation of fundraising was dominated by non-profit sharing deposit contracts and in terms of fund distribution, it was dominated by murabahah and musyarakah contracts. The total fund had allocated into the community exceeds the total funds that raised. Other contracts are still constrained by several factors that are inhibiting and cannot be overcome, including the socialization of products for the collection and distribution of funds, considering that people have only known conventional banks for decades with the interest system